2019
DOI: 10.31258/jes.3.3.p.433-444
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Critical Thinking Skills Through Natural Science Learning Based on the Integration of Guided Inquiry with Numbered Heads Together

Abstract: Process of science learning stresses on giving students direct experience to develop their competence. Therefore, teachers are required to be creative and innovative to improve students’ critical thinking. Accordingly, there is a need for a research on “The science learning based on guided inquiry integration with Numbered Heads Together (NHT) toward critical thinking skill”. This research aim to figure out of influence of the science learning based on guided inquiry integration with NHT. This research is a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The ability to provide or draw conclusions will be followed by skills in selecting valid information. Syafaren, et al (2019) also revealed that critical thinking skills require various reasons and clear information to be synthesized and then synthesized until the information is perfectly accepted. Through information literacy-based learning, it will have a positive impact on how students access information, plan search methods, and how to use information.…”
Section: Correlation Between Critical Thinking and Information Literacymentioning
confidence: 99%
“…The ability to provide or draw conclusions will be followed by skills in selecting valid information. Syafaren, et al (2019) also revealed that critical thinking skills require various reasons and clear information to be synthesized and then synthesized until the information is perfectly accepted. Through information literacy-based learning, it will have a positive impact on how students access information, plan search methods, and how to use information.…”
Section: Correlation Between Critical Thinking and Information Literacymentioning
confidence: 99%
“…Research by Janbuala et al (2013), found that scientific learning can improve student KPS. Learning science not only develops student KPS, but students also gain learning experiences that they experience to develop their competence (Syafaren et al, 2019).…”
Section: Results Of Students' Science Process Skillsmentioning
confidence: 99%
“…Studi lain menyatakan bahwa kreativitas umum merupakan dasar untuk menumbuhkan keterampilan berpikir kreatif [11]. Selain itu, metode pembelajaran Numbered Heads Together (NHT) juga terbukti efektif dalam meningkatkan kemampuan berpikir kritis siswa [12]. Dari beberapa penelitian yang relevan, masih jarang ditemukan penelitian yang mengangkat tema pendekatan problem posing dalam pembelajaran fisika untuk meningkatkan kemampuan berpikir kreatif dan kritis.…”
Section: Pendahuluanunclassified